2022
DOI: 10.1002/ped4.12336
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute hepatitis of unknown causes in children – Current findings, questions, opinions, and recommendations, a mini‐review

Abstract: Since October 2021 in Alabama, the United States, and March 2022 in central Scotland, the United Kingdom, the number of cases of severe acute hepatitis of unknown etiology/causes in children was found to increase, and the total number of cases has reached 920 worldwide by June 22 this year, 45 cases (5%) required liver transplantation, and 18 cases (2%) died according to World Health Organization (WHO). To understand the basic characteristics of this disease/syndrome, a literature search was performed at PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
2
0
2
Order By: Relevance
“…Acute hepatitis is something condition that occurs when the heart experience inflammation caused by a viral infection. Otherwise detected and treated with the fast condition, this can cause damage permanent to the heart, even death, because that is important for parents to get training in detecting early acute hepatitis in children them (Zhaori, 2022).…”
Section: B Discussionmentioning
confidence: 99%
“…Acute hepatitis is something condition that occurs when the heart experience inflammation caused by a viral infection. Otherwise detected and treated with the fast condition, this can cause damage permanent to the heart, even death, because that is important for parents to get training in detecting early acute hepatitis in children them (Zhaori, 2022).…”
Section: B Discussionmentioning
confidence: 99%
“…Es necesario realizar las pruebas de daño hepático (AST, ALT, fosfatasa alcalina, GGT), así como las pruebas de función hepática (bilirrubina total y conjugada, albúmina, INR). Parte de las pruebas deben incluir la valoración de hepatitis virales agudas (serología para hepatitis A, B, C, D, y E), además de otros virus como EBV, CMV y VIH (Zhaori, 2022). También de acuerdo con el contexto epidemiológico de hoy en día, se deben tener en consideración los virus respiratorios (adenovirus, influenza A y B, SARS-CoV-2) y patógenos específicos del sistema gastrointestinal (identificación de adenovirus y rotavirus en heces, coprocultivo).…”
Section: Diagnósticounclassified
“…También de acuerdo con el contexto epidemiológico de hoy en día, se deben tener en consideración los virus respiratorios (adenovirus, influenza A y B, SARS-CoV-2) y patógenos específicos del sistema gastrointestinal (identificación de adenovirus y rotavirus en heces, coprocultivo). El gold standard para determinar los cambios patológicos y patógenos en el tejido hepático es la biopsia además brinda información del proceso disruptivo en el hígado (Uwishema et al, 2022;Zhaori, 2022;Gao et al, 2022).…”
Section: Diagnósticounclassified
“…An initial report from the United Kingdom in early April 2022 of an increased number of children with acute hepatitis of unknown origin (HUO) gained attention worldwide and led to reports of more than 1000 children with HUO two months later. An interim review of the published cases up to June 2022 [1] showed that 45 cases (5%) of the 920 probable cases required liver transplantation and 18 cases (2%) died. An international online survey affirmed the impression that there was indeed an increase in acute hepatitis in 2022 compared to the previous 5 years.…”
Section: Introductionmentioning
confidence: 99%